INHIBITORY ACTIVITY OF ENDOPHYTIC FUNGI ISOLATED FROM SUKABUMI TURMERIC PLANT (Curcuma longa L.) AGAINST MCF-7 CELL LINE - Ratih Asmana Ningrum; Bustanussalam Bustanussalam; Popi Hadi Wisnuwardhani; Neng Herawati; Adi Santoso; Partomuan Simanjuntak (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
Kunyit or turmeric plant (Curcuma longa L.) is a native Southeast Asia plant that has been widely used as herbal medicine. In our previous research we isolated and screened 44 of endophytic fungi of turmeric plant from Sukabumi and Cibinong to determine their antioxidant activity. There were 4 samples isolated from Sukabumi with antioxidant activity for more than 70% at concentration of 100ppm, K.Cl.Sb.R9 (93%), K.Cl.Sb.A11 (81%), K.Cl.Sb.B1 (79%) and K.Cl.Sb.R11 (71%). This research aimed to determine inhibitory activity of the endophytic fungi against estrogen positive MCF-7 breast cancer cell line. To obtain the filtrate, the broth cultures were filtered and the extracellular fraction was extracted with ethyl acetate. The inhibitory activity was determined by using MTT assay. The result showed that the ability of endophytic fungi to inhibit MCF-7 growth was dose dependently. IC50 of endophytic fungi K.Cl.Sb.R9 was 579±38 ppm, K.Cl.Sb.R11 was 542±21ppm, K.Cl.Sb.B1 was 446±15ppm and K.Cl.Sb.A11 was 520±28ppm. Fluorescent double staining based method using calcein AM and ethidium bromide was performed to confirm the inhibitory activity. At 500ppm of filtrate concentration with 24h of cell treatment, treated cell lines showed fewer viable cells compared to untreated cell lines. The four isolates of endophytic fungi were able to inhibit proliferation of human breast cancer MCF-7 cell line.